1996
DOI: 10.2116/analsci.12.431
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Procedure for Trace Analysis of Platinum(IV) in Its Allied Materials

Abstract: Egypt 4-Phenylthiosemicarbazide (HPTS) was investigated as a new collector for the flotation of platinum(IV). The metal ion forms a (1: 2) pale green complex with HPTS in the aqueous solution. An intense clear green layer was formed, after flotation, by adding oleic acid (HOL) surfactant. The composition of the float is 1: 2 (Pt : HPTS). A highly selective and sensitive spectrophotometric procedure was proposed for the determination of microamounts of Pt(IV) as its floated complex. The flotation-determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…17 A flotation technique is recommended as an effective and less-expensive separation and preconcentration tool with most of the advancing factors. [18][19][20][21][22] It involves the removal of surface inactive ions from an aqueous solution with the aid of air bubbles using three modes: adsorptive flotation, precipitation flotation or adsorbing-particle flotation. 22 A process based on solid-phase extraction (SPE) has received more acceptance due to a number of possible advantages, including the availability and easy recovery of the solid phase, the attainability of a large preconcentration factor and a facility for separation.…”
Section: Introductionmentioning
confidence: 99%
“…17 A flotation technique is recommended as an effective and less-expensive separation and preconcentration tool with most of the advancing factors. [18][19][20][21][22] It involves the removal of surface inactive ions from an aqueous solution with the aid of air bubbles using three modes: adsorptive flotation, precipitation flotation or adsorbing-particle flotation. 22 A process based on solid-phase extraction (SPE) has received more acceptance due to a number of possible advantages, including the availability and easy recovery of the solid phase, the attainability of a large preconcentration factor and a facility for separation.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Consequently, such a process enabled and facilitated the spectrophotometric determination of the analyte.…”
Section: Flotation-separation Of V(iv)mentioning
confidence: 99%
“…On the other hand, methods for the separation and preconcentration of metals by flotation, followed by their spectrophotometric determination, have increased in popularity in recent years. [9][10][11][12][13][14][15][16][17][18] A literature survey showed that ion-flotation followed by spectrophotometric determination of V(IV) is rarely reported. 19 Also, no attempt has been found for using 1-(2-hydroxy-4-methoxybenzophenone)-4-phenylthiosemicarbazone (HMBPT) in this concern.…”
mentioning
confidence: 99%
“…6 The use of thiohydrazides such as o-hydroxythiobenzhydrazide, 7 thiobenzhydrazide, 8 α-naphthalenethiocarboxhydrazide, 2-pyrrolthiocarboxhydrazide, furanthiocarboxhydrazide, thiophenethiocarboxhydrazide, 9 dibenzylidenethiocarbohydrazide, 10 and 2-furancarbothioic acid hydrazide 11 in the spectrophotometric determination of rhenium and platinum group metals has been described in a number of papers. Other reagents such as dithizone, 12 anisaldehyde-4-phenyl-3-thiosemicarbazone, 13 dithizone-polyurathane, 14 4-phenylthiosemicarbazide, 15 3-(2′-thiazolylazo)-2,6-diaminopyridine, 16 N-(m-methylphenyl)-N′-(sodium p-aminobenzenesulfonate)-thiourea, 17 piperonal thiosemicarbazone, 18 and leuco xylene cyanol FF, 19 have been reported for spectrophotometric determination of platinum after liquid-liquid extraction. The reagents phenanthrenequinone monoximes 20,21 and 1-(2-pyridylazo)-2-naphthol 22 have been used for spectrophotometric determination of platinum after solid-liquid extraction.…”
Section: Introductionmentioning
confidence: 99%
“…These methods suffer from some drawbacks, such as a longer waiting period for color development, 7,9 a need for multiple extractions for quantitative recovery of the metal, 8 presence of stannous chloride, 12,14 narrow pH range, 10,13,19 high molarity of aqueous phase, 14,16 low absorptivity, 15 low sensitivity 13,20 and low stability of the reagents, [7][8][9] as shown in Table 1. None of these methods allow the separation and separate determination of platinum and rhenium.…”
Section: Introductionmentioning
confidence: 99%